2021
DOI: 10.1080/02813432.2021.2004754
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing in Danish general practice in the elderly population from 2010 to 2017

Abstract: Objective This study aimed to describe prescription of antibiotics to the elderly population in general practice in Denmark from 2010–2017. Design This is a national register-based observational study. Setting General practice, Denmark Main outcome measure The main outcome measure was prescriptions/1,000 inhabitants/day (PrID) in relation to year, age and sex, indication, and antibiotic agent. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Palacios-Cena et al also reported an increasing consumption of J01 prescriptions in elderly subjects from 2003 to 2014 in Spain [ 33 ]. In Denmark, between 2016–2017, an antibiotic consumption of 14.7 DID (65–74 years) and 41.3 DID (≥85 years) was observed in the elderly [ 34 ], while in the period of 2006–2015 in Ontario (Canada), the average consumption among almost 3 million elderly patients was 25.1 DID, with an average prevalence of 40.7% [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Palacios-Cena et al also reported an increasing consumption of J01 prescriptions in elderly subjects from 2003 to 2014 in Spain [ 33 ]. In Denmark, between 2016–2017, an antibiotic consumption of 14.7 DID (65–74 years) and 41.3 DID (≥85 years) was observed in the elderly [ 34 ], while in the period of 2006–2015 in Ontario (Canada), the average consumption among almost 3 million elderly patients was 25.1 DID, with an average prevalence of 40.7% [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Danish National Prescription Register is linked to the CRS and contains individual-level data for all prescribed medications redeemed at Danish community pharmacies since 1995, representing approximately 90% of all antimicrobial prescriptions in Denmark 13. Medications are coded according to the Anatomical Therapeutic Chemical system 14. Available data include medication identification codes and dates the prescriptions were filled.…”
Section: Methodsmentioning
confidence: 99%
“…Pivmecillinam is mainly used in the Nordic countries but is an interesting option as resistance levels have remained low, despite high use for many years [ 12 ]. In the elderly population it is the most commonly prescribed antibiotic agent [ 24 ].…”
Section: Discussionmentioning
confidence: 99%